PTU-015 Trainee Endoscopic Procedures by Deanery and Year of Training in the United Kingdom: August 2011 to July 2012. are we doing Enough?. (4th June 2013) - Ambrose, T; Dunckley, P; Ellis, A
Abstract : Introduction: The burden of acute medicine on specialty trainee registrars (StR) is rising. Anecdotal evidence suggests that fewer endoscopic procedures are being performed by gastroenterology (GI) StR's and that trainees although competent at the time of being awarded their CCT may have less confidence in their endoscopic skills when compared to a historical cohort. The annual review of competency progression (ARCP) decision aid includes indicative numbers of procedures which should be undertaken annually. Since September 2010 all endoscopic procedures undertaken by UK GI trainees have been recorded on a national electronic record (the Joint Advisory Group Endoscopy Training System (JETS)). Methods: We obtained anonymised records from the JETS database for the period 3 August 2011 – 31 July 2012. We analysed the data by trainee grade (ST3–7, locum appointment for training (LAT's)), deanery, numbers and type of procedure, and annual numbers of endoscopy lists (dedicated training, ad-hoc training, and service). Duplicate entries & blank entries were removed. Results: A total of 721 records were obtained from the 19 UK deaneries. 183 blank records were deleted leaving 538 for analysis. 49 (9.1%) were ST3 trainees, 101 (18.8%) ST4, 142 (26.4%) ST5, 120 (22.3%) ST6, 102 (18.9%) ST7, and 24 (4.5%) LAT. Significant variation was seen between trainees both within individual deaneries and between deaneries. The median exposure to endoscopic units (OGD/flexi = 1 unit; colon = 2 units) increased from ST3-ST6 (112–218–275–304) before tailing off at ST7 (227). LAT trainees performed fewer endoscopic units (median 97 units). This pattern was also seen for median number of procedures. Numbers of colonoscopies were generally low across all deaneries. 8 deaneries outperformed the ARCP targets for overall procedures performed at ST3 level and this was accounted for largely by OGDs. Few deaneries met the published targets at ST4-ST7 level. Trainees performed an average of 31 training lists each year (range 0–134; median 29) and 12 service lists (range 0–210) the latter of which were largely, but not entirely, restricted to senior trainees in this dataset. Conclusion: Trainees are performing fewer procedures than recommended in the ARCP guidelines. The variation in endoscopy numbers both between and within trainee grade and deanery suggest factors which can be explored to optimise future opportunities. This analysis should be undertaken regularly to inform The Training Committee of future trends in endoscopic training. Disclosure of Interest: None Declared